PENGARUH KUALITAS DAN CITRA WARDAH: ANALISIS KEPUTUSAN PEMBELIAN DI KALANGAN MAHASISWI POLITEKNIK NEGERI BANDUNG - Nurnajmi, Difa Nasywa; Nisanur, Visi Aulia (Media Mahardhika, 2025)
This study investigates the influence of brand image and product quality on the purchasing decisions of Wardah cosmetic products among female students at Politeknik Negeri Bandung. Using a quantitative descriptive method, the research surveyed 80 respondents aged 17–25 who have purchased Wardah products at least twice. Results reveal that brand image significantly impacts purchasing decisions, with a correlation coefficient of 0.895, indicating a strong relationship. Meanwhile, product quality also influences purchasing decisions, though to a lesser extent, with a correlation coefficient of 0.786. The regression analysis indicates that 81.1% of the variation in purchasing decisions can be explained by the combination of brand image and product quality. These findings suggest that while both factors are important, brand image plays a more dominant role in influencing consumer choices. This study highlights the critical need for companies to invest in brand development and quality improvements to cater to consumer preferences effectively.